Clinico-pathological predictors of clinical complete response in rectal cancer. (2022) - Mbanu, P.; Osorio, E. Vasquez; Mistry, H.; Malcomson, L.; Yousif, S.; Aznar, M.; Kochhar, R.; Van Herk, M.; Renehan, A.G.; Saunders, M.P.
Highlights: Prediction of clinical complete response is essential for treatment selection in organ preservation management of rectal cancer. The use of routine clinical variables can be useful in the prediction of clinical complete response in rectal cancer. A nomogram of routinely available clinical variables can be used to successfully predict complete response in rectal cancer before the commencement of treatment. Abstract: Purpose: Prediction of clinical complete response in rectal cancer before neoadjuvant chemo-radiotherapy treatment enables treatment selection. Patients predicted to have complete response could have chemo-radiotherapy, and others could have additional doublet chemotherapy at this stage of their treatment to improve their overall outcome. This work investigates the role of clinical variables in predicting clinical complete response. Method: Using the UK-based OnCoRe database (2008 to 2019), we performed a propensity-score matched study of 322 patients who received neoadjuvant chemoradiotherapy. We collected pre-treatment clinic-pathological, inflammatory and radiotherapy-related characteristics. We determined the odds for the occurrence of cCR using conditional logistic regression models. We derived the post-model Area under the Curve (AUC) as an indicator of discrimination performance and stated a priori that an AUC of 0.75 or greater was required for potential clinical utility. Results: Pre-treatment tumour diameter, mrT-stage, haemoglobin, alkaline phosphate and total radiotherapy depths were associated with cCR on univariable and multivariable analysis. Additionally, neutrophil to lymphocyte ratio (NLR), neutrophil-monocyte to lymphocyte ratio (NMLR), lymphocyte count and albumin were all significantly associated with cCR on multivariable analysis. A nomogram using the above parameters was developed with a resulting ROC AUC of 0.75. Conclusion: We identified routine clinic-pathological, inflammatory and radiotherapy-related variables which are independently associated with cCR. A nomogram was developed to predict cCR. The performance characteristics from this model were on the prior clinical utility threshold. Additional research is required to develop more associated variables to better select patients with rectal cancer undergoing chemoradiotherapy who may benefit from pursuing a W&W strategy.